Critical information literacy : foundations, inspiration, and ideas - Downey, Annie, 1974- (Sacramento: Library Juice press, 2016)
"Provides a snapshot of the current state of critical information literacy as it is enacted and understood by academic librarians"--
Creating informed citizens in the network society : problematizing the legacy of standards-based information literacy -- The theoretical foundations of critical information literacy -- The revelatory power of critical information literacy : how the pioneers found it and its relationship to professional identity -- How critical librarians teach : methods in context -- What critical librarians teach : avoiding the banking concept with critical content -- Creating a supportive teaching culture for librarians : institutionalizing (critical) information literacy -- The profession : challenges, strategies, and possibilities.
Includes bibliographical references and index.
Keywords: Information literacy; Information literacy -- Study and teaching (Higher); Academic libraries -- Relations with faculty and curriculum; Academic librarians -- Professional relationships; Critical pedagogy; Transformative learning